Patrimônio territorial integrado e espaço cotidiano : o planejamento urbano interativo do Centro de Vitória (ES) - Brambati, Alice Dellabianca (2014)
The concept of territorial and cultural heritage extends the traditional concept of heritage, according to which the monument is restricted to its materiality and remains isolated from its territory. The ambience and the experience of this heritage gain i